2009
DOI: 10.1590/s1982-56762009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Evidencias microscópicas y moleculares de la presencia de fitoplasmas en plantas de murta (Ugni molinae Turcz: ) afectadas por la enfermedad "escoba de bruja"

Abstract: RESUMENLa murta o murtilla (Ugni molinae Turcz., Myrtaceae), es un arbusto frutal siempre verde, nativo de Chile. Su fruto es una baya globosa muy aromática y sabrosa, de gran potencial en consumo fresco e industrializado. El arbusto presenta en el follaje una enfermedad caracterizada por una incontrolable ramificación conocida como "escoba de bruja", siendo la más común y destructiva, la cual podría estar relacionada con un agente biótico. Se realizaron cortes histológicos en tejidos con y sin síntomas de la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The main characteristic of this disease is an uncontrolled branching associated with biotic factors. Moreover, this plant disease is characterized by a reduction in the size of shoots and overgrowth of these; the leaves become smaller and tighten acquiring a reddish to yellowish color, not allowing the development of fruits and when they reach some develop, have a bad taste (Andrade et al, 2009 Aguilera et al (2009) reported that this disease was found in some experimental plots cultivated with U. molinae in the Region of La Araucanía. The Margalef index for wild species was higher (12.98) than other reports for cultivated ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristic of this disease is an uncontrolled branching associated with biotic factors. Moreover, this plant disease is characterized by a reduction in the size of shoots and overgrowth of these; the leaves become smaller and tighten acquiring a reddish to yellowish color, not allowing the development of fruits and when they reach some develop, have a bad taste (Andrade et al, 2009 Aguilera et al (2009) reported that this disease was found in some experimental plots cultivated with U. molinae in the Region of La Araucanía. The Margalef index for wild species was higher (12.98) than other reports for cultivated ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasma infection usually results in dwarfism and leaf alterations (Camarena & De la Torre 2008, Andrade et al 2009). Here we found that symptomatic branches of U. molinae were smaller, thinner, and had smaller leaves (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Plants affected by the disease show increased branching, dwarfism, and color change in affected branches (Lee et al 2000, Camarena & De la Torre 2008, Andrade et al 2009. The phytoplasm infects the phloem of the plant (Andrade et al 2009, Arismendi et al 2010, 2011, altering normal vegetative development. Fruit set is decreased and fruits, when present, have bad flavor (personal observation, Andrade et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation